Public funding of higher education - Jean-Marie Viaene; Itzhak Zilcha (Center for Economic Studies and ifo Institute (CESifo), 2011)
Recent criticism from different sides has expressed the view that, with scarce resources, there is little justification for massive public funding of higher education. Central to the debate is the conjecture that colleges and universities use their resources inefficiently and focus insufficiently on their mission to expand students' human potential. Our aim in this paper is to examine the theoretical premises of this conjecture in a small open economy and uncover the conditions under which public investment in higher education is efficient and desirable. We analyze non-stationary equilibria of an OLG economy, characterized by perfect capital mobility, intergenerational transfers and a hierarchical education system. The government uses income tax revenues to finance basic education and support higher education that generates skilled labor. Given this, the following issues are considered: (a) the impact of education and international markets on the equilibrium number of low-skilled and skilled workers in each generation; (b) the economic efficiency of public subsidies to higher education in generating skilled human capital; (c) the endogenous support for a government's educational policies found in a political equilibrium.
Keywords: D91; E25; H52; 330; hierarchical education; innate ability; capital mobility; education policy; low-skilled workers; skill formation